2020
DOI: 10.12982/cmujns.2020.0041
|View full text |Cite
|
Sign up to set email alerts
|

Elements May Not Be Homogenously Distributed throughout The Bone, an Issue of Concern When Using X-Ray Fluorescence in Species Classification

Abstract: One major question that arises when we talk about the elements in bones is whether all bones contain the same elements. This study was implemented to answer this question and determine what the elemental levels are in the femur bones of pigs using the handheld X-ray fluorescence technique. Ten dry femur bones taken from adult domestic pigs (Sus scrofa domesticus) were scanned using a handheld XRF analyzer. We compared three different groups in this study. First, comparisons were made between six locations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, it was revealed that the elements were not equally distributed in every bone in the body. In 2020, it was conclusively proven that the elements were not equally distributed throughout the bones (Pitakarnnop et al 2020). Moreover, it was found that high Mn and Fe values were identified in severe grades of the OA bone.…”
Section: Elemental Studymentioning
confidence: 99%
“…Furthermore, it was revealed that the elements were not equally distributed in every bone in the body. In 2020, it was conclusively proven that the elements were not equally distributed throughout the bones (Pitakarnnop et al 2020). Moreover, it was found that high Mn and Fe values were identified in severe grades of the OA bone.…”
Section: Elemental Studymentioning
confidence: 99%